PANTANGAN DAN LARANGAN DALAM KEHIDUPAN MASYARAKAT KAJANG: ANALISIS ETNOGRAFI TERHADAP NILAI BUDAYA - Amirullah; Sarna Pasawin; Ridha, Muh. Rasyid; P, Stefanny Datu; Arif , Muh. Al Awwal Ilham Wal (IAIN Parepare, 2025)
This research examines the abstinence and prohibition system of the Kajang community in South Sulawesi, analyzing its form, meaning, cultural value, and role in maintaining social order and cultural identity. Descriptive qualitative method with ethnographic approach was used through literature study and observation to understand the resilience of customary rules in the midst of modernization. The results show that customary taboos cover aspects of life such as dress code, social interaction, natural resource management, and rituals, with philosophical values of simplicity, equality, obedience, and natural harmony. The Ammatoa's central role as customary leader is key to maintaining the continuity of this value system through norm enforcement and intergenerational transmission. In conclusion, the customary abstinence system functions as an effective instrument of social regulation, as well as a protector of cultural identity. This research confirms the importance of local wisdom in shaping sustainable communities with strong identities amidst global changes. The findings provide a perspective on the relevance of tradition preservation as a foundation of cultural resilience.